Thermal Stability and Structure-gas Transport Property Relationships for Nanoporous Cyanate Ester Resins - Gusakova, Kristina; Fainleib, Alexander; Espuche, Eliane; Saiter, Jean-Marc; Grigoryeva, Olga; Starostenko, Olga; Gouanve, Fabrice; Grande, Daniel (Scientific Research, New Technologies and Applications Vol. 4, 2024)
This chapter discloses the relationships between the structure, thermal and gas transport properties of nanoporous thermostable cyanate ester resins (CERs). The nanoporous CERs were derived from the polycyclotrimerization of 1,1'-bis(4-cyanatophenyl) ethane with 30 or 50 wt% of inert high-boiling temperature dimethyl- or dibutyl phthalates, followed by their quantitative removal. Porous structure in the CER-based films was generated through a chemically induced phase separation process, with subsequent porogen extraction from the densely crosslinked CERs. The structure and morphology of the nanoporous films produced were investigated by FTIR and SEM techniques, respectively. The pore sizes ranging from Dp ~ 10 to 120 nm in the samples obtained were observed. To achieve complete desorption of the porogen moieties from the networks, an additional thermal annealing at 250oC was performed. The annealing behavior and thermal stability of nanoporous film materials were also studied in detail. Gas transport properties of the nanoporous CER films were analyzed following various processing steps. The relationships between the CER structure and the key gas transport parameters were determined. The final porous materials are characterized by high thermal stability, with glass transition temperatures exceeding 214oC.